Signaling diversity enabled by Rap1-regulated plasma membrane ERK with distinct temporal dynamics - Keyes, Jeremiah; Ganesan, Ambhighainath; Molinar-Inglis, Olivia; Hamidzadeh, Archer; Zhang, Jinfan; Ling, Megan; Trejo, JoAnn; Levchenko, Andre; Zhang, Jin (eLife, 2020)
A variety of different signals induce specific responses through a common, extracellular-signal regulated kinase (ERK)-dependent cascade. It has been suggested that signaling specificity can be achieved through precise temporal regulation of ERK activity. Given the wide distrubtion of ERK susbtrates across different subcellular compartments, it is important to understand how ERK activity is temporally regulated at specific subcellular locations. To address this question, we have expanded the toolbox of Förster Resonance Energy Transfer (FRET)-based ERK biosensors by creating a series of improved biosensors targeted to various subcellular regions via sequence specific motifs to measure spatiotemporal changes in ERK activity. Using these sensors, we showed that EGF induces sustained ERK activity near the plasma membrane in sharp contrast to the transient activity observed in the cytoplasm and nucleus. Furthermore, EGF-induced plasma membrane ERK activity involves Rap1, a noncanonical activator, and controls cell morphology and EGF-induced membrane protrusion dynamics. Our work strongly supports that spatial and temporal regulation of ERK activity is integrated to control signaling specificity from a single extracellular signal to multiple cellular processes.
Keywords: ERK; PC12; spatiotemporal; EGF; Rap1; signal transduction